1997
DOI: 10.5636/jgg.49.supplement_s49
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Large Enhancements of the Jovian Decameter Radio Bursts Caused by the Magnetosphere-Plasmasphere Passages of Shoemaker-Levy 9 Comet Fragments-Evolution of Jovian Decametric Radiation Feature into the State of Intense Decametric Pulsar

Abstract: Observation results of the Jovian decameter wave emissions in the period of the passages of fragments of Shoemaker-Levy 9 comet through the Jovian magnetosphere indicated extremely large enhancements of Jovian decameter wave radiations (JDR), being caused by dust-plasma clouds moving across the Jovian magnetic fields. The total emission power of the decameter wave radiations was increased to the level of approximately 10 times larger than the regular maximum level of the emissions of the Jovian decameter radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
(11 reference statements)
2
1
0
Order By: Relevance
“…8, which corresponds to the previously-reported result (Carr et al, 1983), however, the former peak (60 • ≤ CML ≤ 180 • ) is too high relative to the latter peak (180 • ≤ CML ≤ 300 • ). In fact, the obtained result is more similar to that reported by Oya et al (1997) who pointed out the possibility the occurrence probability is influenced by the fragments of SL-9 comet. About the emissions from 60 • to 180 • in CML except for well known Io-B emissions, we calculate the dependence of occurrence probabilities on Io phase.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…8, which corresponds to the previously-reported result (Carr et al, 1983), however, the former peak (60 • ≤ CML ≤ 180 • ) is too high relative to the latter peak (180 • ≤ CML ≤ 300 • ). In fact, the obtained result is more similar to that reported by Oya et al (1997) who pointed out the possibility the occurrence probability is influenced by the fragments of SL-9 comet. About the emissions from 60 • to 180 • in CML except for well known Io-B emissions, we calculate the dependence of occurrence probabilities on Io phase.…”
Section: Resultssupporting
confidence: 89%
“…The technique proposed in this study is based on Fourier transform of observed interferometer data; this provides useful tool to detect the weak Jovian emission out of background noise by calculating the correlation coefficient between observed and theoretical fringe wave form of the interferometer. As the results of data analyses by using the data set obtained from 2007 to 2010, we found the similar dependence of occurrence probabilities on CML to that reported by Oya et al (1997). It is clarified that the occurrence probability of emissions detected in the non-Io-B region which is defined as sources associated with 60 to 180 degrees in CML has a clear dependence on the Io-phase around 240 degrees; we may state appearance of a new Io related source.…”
Section: Summary and Future Studysupporting
confidence: 84%
See 1 more Smart Citation